Trends of Opioid Use Disorder Among Hospitalized Patients With Chronic Pain. Issue 6 (17th June 2019) - Orhurhu, Vwaire; Olusunmade, Mayowa; Urits, Ivan; Viswanath, Omar; Peck, Jacquelin; Orhurhu, Mariam Salisu; Adekoya, Peju; Hirji, Sameer; Sampson, John; Simopoulos, Thomas; Jatinder, Gill
Abstract: Background: Patients with chronic pain treated with opioids are at an increased risk for opioid misuse or opioid use disorder (OUD). Recent years have seen a stark increase in abuse, misuse, and diversion of prescription opioid medications. The aim of this study was to investigate trends in changing rates of opioid use disorder among patients with chronic pain. Methods: The National Inpatient Sample (NIS) database identified chronic pain admissions with OUD from 2011 to 2015. Patients were identified from the NIS database using International Classification of Diseases (9th and 10th revisions) diagnosis codes for chronic pain and OUD. Annual estimates and trends were determined for OUD, patient characteristics, OUD among subgroups of chronic pain conditions, and discharge diagnosis. Results: We identified 10.3 million patients with chronic pain. Of these, 680, 631 patients were diagnosed with OUD. The number of patients with OUD increased from 109, 222 in 2011 to 172, 680 in 2015 ( P < 0.001). Similarly, there were upward trends of OUD among females (53.2% to 54.5%; P = 0.09), patients 65 to 84 years of age (11.8% to 17%; P < 0.001), Medicare‐insured patients (39.5% to 46.0%; P < 0.01), patients with low annual household incomes (27.8% to 33.3%; P < 0.001), and patients with cannabinoid use disorder (7.2% to 8.3%; P = 0.01). The prevalence of OUD increased from 2011 to 2015 in patients with chronic regional pain syndrome (5.53% to 7.46%; P = 0.01) and spondylosis (1.32% to 1.81%; P < 0.001). Conclusions: These findings suggest that the prevalence of OUD increased substantially from 2011 to 2015. Disparities of OUD with increasing opioid use among vulnerable populations including women, those with Medicare insurance, tobacco use disorder, and low annual income should be explored further.